Experimental and numerical analysis on the bending response of the geometrically gradient soft robotics actuator (Archives of Mechanics - Test, 2018)
In this study, three different soft pneumatic actuators (SPA) are designed and directly fabricated through additive manufacturing using thermoplastic polyurethane (TPU) filaments. The equal total inner volume size is used in the three varied designs to compare their effect on the bending response. A material model is selected and implemented according to the uniaxial tensile test parameters. The experimental results obtained from three different soft pneumatic actuators are compared with numerical model results. Especially, the experimentally measured bending forces are compared with the numerical model counterparts. The highest continuous bending deformation is determined among the three different soft pneumatic actuators. Additionally, a new integrated design and manufacturing approach is presented aiming to maximize the potential bending capability of the actuator through additive manufacturing.